63.2k views
6 votes
What is the sum? 2x/x^2 + x-4/9x​

User Azuan
by
5.1k points

1 Answer

0 votes

Answer:(x² + 14x)/(9x²)

Explanation:

Explanation:To do this calculatio process:The first term: 2x/x² = 2/x.Then: (2/x) + (x - 4)/(9x).We should common the denominator by multiplying the denominators of the two terms (9x)(x) = 9x² and dividing each denominator by the common denominator.So, it will be equal:[(2)(9x) + (x - 4)(x)]/9x² = (18x + x² - 4x)/9x² = (x² + 14 x)/9x².

User Cyril Bvt
by
4.7k points